Water source quality testing in Gezira State, Sudan, using the compartment bag test - Abdelgalili, Eltigani Bashier (Appl Water Sci, 2019)
Although poor water quality is recognized as a public health threat, it has been little investigated in Sudan. In this paper, water sources in Gezira State, Greater Wad Medani locality, have been categorized as safe, intermediate safe and high-risk unsafe sources using the compartment bag test (CBT) to detect E. coli, which is an indicator of fecal contamination of water. The CBT is simple, portable and self-contained, and it can be done in the field environment. A total of 122 samples were collected from different water sources and included rivers, water treatment plant, boreholes/tube wells, hand pumps, public water taps, public water coolers, public elevated water tanks and household elevated water tanks. It was found that 69% (84/122) of investigated water sources were safe to drink. The sources most likely to be contaminated were those close to industrial points and factories or open sources exposed to pollution. The result showed that the highest level of contamination of water sources (high risk and unsafe) was observed in rural area (9.1%) followed by urban (5.7%) and peri-urban (1.6%). Frequent and routine qualitative analysis of water sources using CBT is recommended to improve human health and hence the country’s development.